Culturally Responsive Teaching: Its Application in Higher Education Environments - Laveria Hutchison; Leah McAlister-Shields (MDPI AG, 2020)
The application of culturally responsive teaching (CRT) in this article is used to provide a background into the instructional concept of CRT in higher educational settings and to provide examples for classroom pedagogical practice. This article provides instructional approaches that can be used in higher education classes to promote a cultural context to engage preservice teaching candidates who are seeking initial certification to become teachers-of-record and graduate-level teachers who are certified to understand and embrace the intersection of race, gender, religion, and regional cultures that contribute to identity. This article outlines instructional activities that can be used by faculty in higher education programs to assist their students with learning to co-construct culturally responsive lessons. This type of instruction should lead to a process in which faculty in higher educational settings can assist their preservice teacher candidates and graduate-level students in understanding the community in which they will serve or currently serve and to bring the funds of knowledge of their students into positive and productive learning environments.